Small ruminants: What kind of development? - Lebbie, S.H.B. (German Foundation for International Development, 1993)
The importance of small ruminants as valuable renewable resources in the world in general and Africa in particular, is briefly reviewed. Opportunities for increasing their productivity and contribution to the national and/or household income are considerable. Research and Development programmes in the past two decades have focused on adressing constraints to the exploitation of these existing opportunities. The impacts from these efforts have been patchy. The underlying factors for this unhappy situation have been discussed. To produce the desired impact, future small ruminant research and Development programmes should have clear objectives, adapt a farming systems approach, be user-driven, be interdisciplinary in nature, take advantage of and utilize existing research results, adress post-production aspects, be environmental friendly and be coordinated through national, regional or internaitonal networks. The restoration of the good image of small ruminants remains the biggest challenge to those who want to promote the welfare of these species.